Step-by-step explanation:
a1 = 27
r = -9/27 = -⅓
the formula :
an = a1. r^(n-1)
= 27. (-⅓)^(n-1)
= 3³(-3`¹)^(n-1)
= 3³(-3)^(1-n)
Answer:
2x - 5
Step-by-step explanation:
2x + 4 - 9
the 2x gonna stay
so you take 4 - 9 = -5
so the answers gonna be 2x - 5
bc the 5 is negative so you gonna subtract
I hope you understand my english...
Answer:
-11 + 4
Step-by-step explanation:
When you subtract a negative the sign will switch to plus, so it this case you would switch the - (-4) to a + 4 but you don't change the -11 at the front.
Answer:
117 i think
Step-by-step explanation:
Well, variables are stuff like x and y because they can represent a number. They are variable in an equation. so if you have (3x^3)+(5X^2)+Y+9 then your variables are x X and Y (im assuming the capital X is there and not a typo) if that was a typo and meant to be lowercase, then its just a 2 variable with the x and y